Aneurysmal Bone Cyst of Thoracic Spine in an Elderly Treated by Two Stage 360° Surgical Excision and Reconstruction with Expandable Cage – A Case Report - T S Nidhin; Ashok Thomas; V Vignesh Kumar; P P Nayar; Davis John (Journal of Orthopaedic Case Reports)
Introduction: Aneurysmal bone cysts (ABCs) are rare, representing about 1% of primary bone tumors and 15% of all primary spine tumors. When they are located in poorly accessible regions such as the spine and pelvis, their management can be challenging. Treatment options include selective arterial embolization, curettage, en bloc excision with reconstruction, and radiotherapy. Case Report: A 68-year-old male presented to the outpatient department with complaints of left flank pain and abdominal pain for 4 months. Clinical examination showed tenderness in the thoracolumbar region with other spine examinations within normal limits. Magnetic resonance imaging dorsal spine showed an expansile lytic multiloculated lesion in the T11 vertebral body with mild extramedullary thoracic cord compression with subtle cord edema. The lesion showed a multiloculated bubbly appearance with fluid-layered locules. He underwent 2 stage procedure. In the first stage, posterior decompression, posterior stabilization, and biopsy were done. The histopathology report was consistent with ABCs. In the second stage, T11 corpectomy, tumor excision, and reconstruction with an expandable cage were done. Postoperatively his pain was reduced and was neurologically intact. At 4-year follow-up, clinically, he has excellent functional outcome and free of recurrence. Conclusion: 360° excision and reconstruction is an effective treatment option for ABCs of spine in the elderly.